1975
DOI: 10.5254/1.3547453
|View full text |Cite
|
Sign up to set email alerts
|

Ground Rice-Hull Ash as a Filler for Rubber

Abstract: A ground rice hull ash prepared by a new burning process has been found to be a moderately reinforcing filler for rubber. This filler, 85-90% amorphous silica and 10-15% carbon, is made by a controlled incineration process in which the bulk of the organic components of the rice hulls is removed, leaving the skeletal silica structure of the hull intact and in the amorphous state. The resultant ash is easily ground to produce fine particles, generally in the range of 0.1-2.0 μm. This filler does not adversely af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 0 publications
2
34
0
1
Order By: Relevance
“…Although the use of husk as fuel to produce the energy necessary in grain processing, as a substitute for oil and coal, is a feasible practice, because it allows reduction in oil expenses, other alternatives are conceivable. 1 An early investigation by Haxo and Mehta 1 proved that ground rice husk ash obtained by means of a special burning process is a moderately reinforcing filler for such rubbers as styrene-butodiene rubber (SBR), ethylene propylene diene methylene rubber (EPDM), and natural rubber (NR). A recent study by Ahmad Fuad et al 2,3 observed that the incorporation of rice husk ash into polypropylene has led to a significant increase in flexural modulus of the composites; that is, comparable to that of such other commercial fillers as mica.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of husk as fuel to produce the energy necessary in grain processing, as a substitute for oil and coal, is a feasible practice, because it allows reduction in oil expenses, other alternatives are conceivable. 1 An early investigation by Haxo and Mehta 1 proved that ground rice husk ash obtained by means of a special burning process is a moderately reinforcing filler for such rubbers as styrene-butodiene rubber (SBR), ethylene propylene diene methylene rubber (EPDM), and natural rubber (NR). A recent study by Ahmad Fuad et al 2,3 observed that the incorporation of rice husk ash into polypropylene has led to a significant increase in flexural modulus of the composites; that is, comparable to that of such other commercial fillers as mica.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size, surface activity and structure are important factors when evaluating a filler for polymer applications. High structure (OAN at or above 200 mL/100g [48]) is desirable for better processing, because homogeneous dispersion is achieved [86]. Additionally, fine primary particle size (10-100nm) is desirable for high reinforcing degree [87].…”
Section: Use Of Rha As Reinforcing Filler In Polymersmentioning
confidence: 99%
“…Other kind of elastomers or elastomer blends have been investigated with RHA as filler, such as styrene butadiene rubber (SBR) [86], epoxidized rubber [75] …”
Section: Rha /Elastomers Compositesmentioning
confidence: 99%
“…Um dos primeiros trabalhos preliminares sobre o uso de cinzas de casca de arroz como carga em polímeros foi reportado em 1975 por Haxo e Mehta 34 , e o uso dessa carga em polietileno foi reportado recentemente por Fuad et al 35 , que observaram um aumento significativo no módulo de flexão do compósito, sendo comparável ao de outras cargas comerciais utilizadas, como por ex., a mica. Entretanto, Ishak e Bakar 36 foram os primeiros que sugeriram a utilização tecnológica de cinzas de casca como carga de borracha.…”
Section: Utilização Da Cinza Como Carga Em Polímerosunclassified